Al-Farabi: Riwayat Hidup, Pemikirannya Tentang Emanasi/Al-Fawdh, Filsafat Jiwa/Al-Nafs, Filsafat Kenabian, dan Teori Politik/Al-Madinah Al-Fadhilah Saida Sahyani - Firmansyah, Fiqih; Santalia, Indo (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Al-Farabi, a great philosopher who lived in the 10th century, is known as the "Second Teacher" after Aristotle, and has a great influence on the development of Islamic philosophical thought. In his biography, Al-Farabi was born in the Farab region (now Kazakhstan) and received his education in various large cities such as Baghdad and Damascus. His thoughts cover various fields, including metaphysics, ethics, politics, and psychology. One of his main ideas is the concept of emanation (al-fawdah), where the world emerged from the all-perfect God, through a continuous process. Al-Farabi also developed a theory of the soul (al-nafs), where the human soul has various levels and can achieve happiness through achieving moral and intellectual perfection. In the field of prophecy, he stated that the prophet is a figure who has an extraordinary ability to receive revelation and provide guidance to humanity, thus enabling the achievement of a good life. His political theory, known as "al-madinah al-fadhilah" or the perfect city, emphasized the importance of a wise and just government, which could lead society towards a harmonious and virtuous life. Al-Farabi's thoughts made significant contributions to the Islamic philosophical tradition and have influenced subsequent schools of thought, both in the Islamic world and the West.